THE EFFECT OF GADGET USE ON CHILD DEVELOPMENT: A PATH ANALYSIS EVIDENCE FROM MELAWI, WEST KALIMANTAN - Calorina, Livia; Pawito, Pawito; Prasetya, Hanung (Journal of Maternal and Child Health, 2020)
Background: The use of gadgets in early childhood can affect the mental and physical development of children. The Indonesian Pediatric Association (IDAI) estimates that 5-10% of children experience developmental delays. Children's development is influenced by environmental factors, parents, nutritional status, and the use of gadgets. This study aimed to analyze the effect of gadget use on child development in Melawi, West Kalimantan, using path analysis model.Subject and Method: This was a cross sectional study conducted in Melawi, West Kalimantan, Indonesia, from August to September 2019. A total 200 children aged 3 to 5 years old was selected by fixed exposure sampling. The dependent variable was child development. The independent variables were gadget usage, maternal age, maternal education, maternal employment, family income, number of children, and family type. The data were collected by questionnaire. The data were analyzed by path analysis run on Stata 13.Result: Child development was directly and positively affected by maternal aged ?20 years old (b= 1.52; 95% CI= -0.29 to 3.35; p= 0.101), high maternal education (b=2.53; 95% CI=1.23 to 3.84; p<0.001), family income ?Rp 2,288,000 (b= 1.38; 95% CI= 0.01 to 2.77; p= 0.049), and core family type (b= 1.61; 95% CI= 0.43 to 2.80; p= 0.008). Child development was directly and negatively affected by gadget use (b= -2.74; 95% CI= -3.99 to -1.49; p<0.001), mother working outside the house (b= -1.98; 95% CI= -3.06 to -0.90; p<0.001), and number of children >2 (b= -2.48; 95% CI= -3.67 to -1.29; p<0.001). Child development was indirectly affected by maternal education and maternal employment.Conclusion: Child development is directly and positively affected by maternal aged ?20 years old, high maternal education, high family income, and core family type. Child development is directly and negatively affected by gadget use, mother working outside the house, and number of children >2. Child development is indirectly affected by maternal education and maternal employment.Keywords: gadget use, child development, path analysisCorrespondence: Livia Calorina. Postgraduate of Public Health Sciences, Sebelas Maret University, Jl. Ir. Sutami 36 A, Surakarta, Central Java 57126. Email: liviacalorina41@gmail.com. Mobile: 081346595497Journal of Maternal and Child Health (2020), 5(1): 111-120https://doi.org/10.26911/thejmch.2020.05.01.12